Adolescents and Young Adults With a "Rare" Cancer: Getting Past Semantics to Optimal Care for Patients With Germ Cell Tumors. (4th June 2014) - Stoneham, Sara J.; Hale, Juliet P.; Rodriguez-Galindo, Carlos; Dang, Ha; Olson, Thomas; Murray, Matthew; Amatruda, James F.; Thornton, Claire; Arul, G. Suren; Billmire, Deborah; Krailo, Mark; Stark, Dan; et al.
Abstract : Because the tumors of adolescence and young adulthood (AYA) are distinct from those that occur earlier and later in life, the most common tumors in this age group are termed "rare." We offer a collaborative, cross-disciplinary, evidence-based approach, advocated and funded by civil society, to advance the field of germ cell tumor and potentially to apply to other rare AYA tumors.